Cetacean bycatch management in regional fisheries management organizations: Current progress, gaps, and looking ahead - Elliott, Brianna; Tarzia, Marguerite; Read, Andrew J. (Frontiers in Marine Science, 2023)
Bycatch is the leading global threat to cetaceans, with at least 300,000 cetaceans estimated to be killed each year in fisheries. Regional fisheries management organizations (RFMOs) are key actors in global fisheries management, including bycatch reduction, but their role in cetacean bycatch management is often overlooked. The primary mandate of RFMOs is to manage fisheries of target stocks, but many of their Convention Agreements call for addressing bycatch of threatened and protected species in their fisheries, including cetaceans. We reviewed 14 RFMOs to understand their current cetacean bycatch management efforts. We developed twenty-five criteria for best practices in cetacean bycatch management to understand efforts made by each RFMO, grouped into five categories: 1) general bycatch governance; 2) observer coverage; 3) quantitative bycatch limits; 4) data analysis and transparency; and 5) mitigation efforts. Collectively, based on our application of these criteria, RFMOs scored highest in “data analysis and transparency” (average=0.74) and lowest in setting “quantitative bycatch limits” (average=0.15). Overall, RFMOs have passed few binding conservation and management measures focused on cetacean bycatch, particularly compared to those addressing the bycatch of seabirds and sea turtles; the few existing measures are primarily focused on bycatch in purse seines. Notwithstanding the United Nations (UN) large-scale drift gillnet ban (46/215) on the high seas, only one RFMO has passed a management measure specifically focused on cetaceans and gillnets, widely recognized as the gear type posing the highest risk to cetaceans. No measure in any RFMO specifically addresses cetacean bycatch in longlines. We provide recommendations to the RFMO community to encourage progress on this critical issue, including leveraging other recent policy developments such as the adoption of the 2021 UN Food and Agriculture Organization Guidelines to prevent and reduce bycatch of marine mammals in capture fisheries and implementation of the U.S. Marine Mammal Protection Act Import Provisions.